A Systematic Review of Franchising as an Alternative Business Model - Zubairu U. M., Ayorinde A. A. & (Covenant Journal of Entrepreneurship, 2018)
In today’s business world, franchising has become a viable alternative business model for expansion to many entrepreneurs. As a result, this paper aims to systematically review underlying issues of franchising systems and make suggestions for further research based on identified gaps. The study adopted the Systematic Quantitative Assessment Technique (SQAT) in analysing 91 English peer-reviewed journal articles from 2009-2018 on franchising from six high quality academic databases: Emerald, Elsevier, Springer, Sage, Taylor and Francis, and Wiley. The study reveals a significant work in franchising articles with 17 and 15 papers out of 91 reviewed articles drawing attention to conflict management and market selection processes respectively. 61 out of 91of the articles were empirical in nature and the theoretical background upon which majority of the papers rested on was Agency theory and Resource Scarcity theory. A large number of the studies were conducted in the USA and Europe, whilst the least were from Africa and none from South America, with survey and Panel data being the most prominent research methods. The study also presented evidence of a growing trend in the number of franchising articles within the ten years. The findings of this research provide an x-ray of discourses on the Franchising research topic, showing intricacies that will serve as guides for existing and prospective researchers in the field. The significant contribution of this study is that it is a new addition to the franchising field, offering insights to act as guides for future researchers.